(untitled) - Frazier, Charles (New York, 1998)
The impact of the Civil War on lovers. Inman is not the man he used to be, as wounded in battle he slowly makes his way home to North Carolina. His sweetheart, Ada, too has changed, no longer a flighty belle but a hard-working farm woman. Will love be the same?
Keywords: Love stories,Chuyện tình,United States,Hoa Kỳ; History,Fiction,Lịch sử,Truyện; Civil War, 1861-1865,Nội chiến, 1861-1865